USING TIKTOK TO PRACTICE SPEAKING SKILLS: EXPERIENCE OF INDONESIAN UNIVERSITY STUDENTS - Nurwinda, Sulistia; Ambarwati, Evi Karlina (Journal of English Educational Study (JEES), 2024)
The rise of technology has led to an increase in the use of technology in education. There are a lot of platforms that can be used for a learning medium, one of them is TikTok. TikTok is a video-sharing app where users can watch or create short videos with various topics, including education. This research was conducted to find out students' experiences while using the TikTok platform as a learning medium to practice speaking skills. This research utilized a qualitative design with a case study as a method. To gain a comprehensive understanding of the participants' experience using TikTok as a learning tool, the research employed a combination of interviews and questionnaires as instruments. This research involved five English education department students as participants. The findings of this research revealed that all participants had a positive experience using TikTok as a learning tool to practice speaking. The study found that participants not only loved TikTok's easy navigation and engaging content but also appreciated its interactive features, particularly the "Duet me" challenge. In conclusion, TikTok is a valuable tool to facilitate students’ learning experience in practicing speaking.